Stressors, allostatic load, and health outcomes among women hotel housekeepers: A pilot study - Rosemberg, Marie-Anne S. (J Occup Environ Hyg, 2019)
Hotel housekeepers are exposed to stressors at work and outside of work. A minimal amount is known about these workers’ pathophysiological responses to those stressors. Allostatic load is a concept increasingly used to understand pathophysiologic manifestations of individuals’ bodily response to stress. The purpose of this study was to examine the associations between work and nonwork stressors, allostatic load, and health outcomes among hotel housekeepers. Work and nonwork stressors (e.g., the number of traumatic events, everyday discrimination, and job strain) and health outcomes (e.g., general health status, physical and mental health, and chronic diseases) were measured. Biometric and anthropometric measures and fasting blood specimens were collected. Blood biomarkers included CRP, HbA1c, HDL, and cortisol. Descriptive analyses, correlations, regressions, and t-tests were conducted. Forty-nine women hotel housekeepers participated, with a mean age of 40 years. One-fifth reported high job strain and more than 40% had at least one traumatic event. Chronic conditions were commonly reported, with about 78%, 55%, and 35% reporting one, two, and three chronic conditions, respectively. Correlation analyses showed that reports of high job strain and everyday discrimination were significantly associated with high ALI quartile score (r=0.39, p=0.011; r=0.41, p=0.004). Job strain and everyday discrimination had medium to large effect sizes on ALI quartile scores. High ALI quartile score was significantly associated with having at least one chronic disease (r=0.40, p=0.005), and it had a large effect size on chronic diseases. To our knowledge, this is the first study to explore allostatic load among hotel housekeepers. Hotel housekeepers have high exposure to stressors within and outside of their work and experience poor chronic conditions. Allostatic load had strong associations with both stressors and health outcomes. Despite this worker group being a hard-to-reach worker group to participate in research studies, this study demonstrates the feasibility of accessing, recruiting and collecting survey data and blood samples among them to determine health risks and guide future targeted interventions.